A combined dynamic analysis method for geometrically nonlinear vibration isolators with elastic rings. (August 2016) - Hu, Zhan; Zheng, Gangtie
Abstract: A combined analysis method is developed in the present paper for studying the dynamic properties of a type of geometrically nonlinear vibration isolator, which is composed of push–pull configuration rings. This method combines the geometrically nonlinear theory of curved beams and the Harmonic Balance Method to overcome the difficulty in calculating the vibration and vibration transmissibility under large deformations of the ring structure. Using the proposed method, nonlinear dynamic behaviors of this isolator, such as the lock situation due to the coulomb damping and the usual jump resulting from the nonlinear stiffness, can be investigated. Numerical solutions based on the primary harmonic balance are first verified by direct integration results. Then, the whole procedure of this combined analysis method is demonstrated and validated by slowly sinusoidal sweeping experiments with different amplitudes of the base excitation. Both numerical and experimental results indicate that this type of isolator behaves as a hardening spring with increasing amplitude of the base excitation, which makes it suitable for isolating both steady-state vibrations and transient shocks. Highlights: A combined method for studying geometrically nonlinear isolators is proposed. This method succeeds in calculating nonlinear vibration under large deformations. The geometrically nonlinear theory is used to find the force and deformation relationship. The Harmonic Balance Method is used to study the nonlinear vibration. The proposed method is validated by both numerical and experimental results.